Caterpillar diet breadth in Área de Conservación Guanacaste, a large and diverse Neotropical wildland in northwestern Costa Rica: toxins, silica, aluminum, and sclerophylly - Quicke, Donald L. J.; Brown, Allison; Hajibabaei, Mehrdad; Manjunath, Ramya; Naik, Suresh; Ratnasingham, Sujeevan; Sones, Jayme; Jacques, Brianne St.; Smith, M. Alex; Zamora, Nelson; Brown, John W.; Matson, Tanner A.; et al. (Frontiers in Ecology and Evolution, 2025)
Caterpillar–food plant records collected over approximately 38 years in the Area de Conservación Guanacaste (ACG) in northwestern Costa Rica are described and summarized. The data comprise 431,212 individual rearing records, 197,366 of which represent unique plant–herbivore associations, i.e., same species pair found on separate dates and at different plants of the same species. These represent 29,187 different caterpillar–food plant associations between 2,489 plant and 7,160 Lepidoptera species. We evaluate changes in the taxonomic composition of the food plant flora and Lepidoptera fauna between 1990 and 2020 and across habitat/community types. Food plant and caterpillar community species richness in the rain forest changed considerably over the first 10 years but remained more stable since. Dry forest communities were more consistent than in rain forest. The cloud forest biota was the most consistent between 1995 and 2010, but as in dry forest, the caterpillar fauna changed considerably during 2015–2020. Plant species composition was more constant than caterpillar composition. The taxonomic distributions of diet specialists and generalists are explored. Most of the species-rich Lepidoptera families contain many specialists, variously concentrated throughout each family, though highly polyphagous collectively. The exceptions include Sphingidae, which show preference for Rubiaceae, Hesperiinae for monocotyledons, and non-Hesperiinae skippers for Fabaceae. Among plant families for which there are over 1,000 independent rearings, Acanthaceae, Apocynaceae, Arecaceae, Costaceae, Melastomataceae, Moraceae, Piperaceae, Poaceae, Rubiaceae, Rutaceae, and Solanaceae hosted the greatest proportion of specialists. However, the level at which dietary specialization corresponds to taxonomic rank varies with both caterpillar and plant taxon. Most fern-feeders are polyphagous with respect to fern families but still specialists on Polypodiopsida. A selection of plant families with conspicuous allelochemical and/or structural defenses and a selection of caterpillars and caterpillar families with equally conspicuous counter-defenses were examined. We determined that (1) unpalatable, aposematic herbivores tend to be specialists and (2) families of plants predominantly consumed by highly defended caterpillars host fewer polyphagous herbivores than families with less conspicuously defended plants. Highly toxic plant families with the fewest rearings, such as Aristolochiaceae and Zamiaceae, hosted many monophagous caterpillars. Biochemical and structural plant defenses appear to mediate herbivore diet breadth for many plant families.